Sistem Traksi Kereta Rel Listrik Dengan Teknologi VVVF - Taufik Hidayat (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2012)
The electrical system of electric railcar with the variable voltage variable frequency (VVVE) technology has been equipped with different devices functioning to change the DC-link voltage from the overhead line in undesired conditions. It also transmits energy powered by the motor due to a braking process not able to be transmitted back to the overhead line, and keeps the DC-link voltage stable during the braking process. The inverter functions to change the DC-link voltage into a source of AC 3 phase whose voltage and frequency can be regulated. The voltage and frequency variables produced are used to power four induction motors. The rotation speed of the motor can be set as desired by regulating the voltage and frequency of the AC source. Another function is to transmit back the force generated by the motor during the braking to the overhead line.